Esophageal lung in an infant - Saeedeh Majidi; Reza Nazarzadeh; Mehran hiradfar; Marjan Joudi; Ahmad mohamadipour; Hosein Tajali (Journal of Pediatric Surgery Case Reports, 2019)
Communicating bronchopulmonary foregut malformations (CBPFMs) or esophageal lung, are rare malformation which define by communication between respiratory system with esophagus or stomach. We presented a case whit esophageal lung, in whom the entire right lung was originated from esophagus. Right pneumonectomy was done and the esophagus was repaired. The aim of this case report is to focus on early diagnosis and proper surgical management.